Measuring radon concentration and toxic elements in the irrigation water of the agricultural areas in Cameron Highlands, Malaysia - Murtadha S. Al-Nafiey; Mohammad S. Jaafar; Sabar Bauk (Universiti Kebangsaan Malaysia, 2014)
Radon and toxic elements (Pb, Cd, Co, Cu, Cr, Zn and Ni) were measured in different water samples in Cameron Highlands, Pahang. RAD7 and rad H20 were used to estimate the radon concentration. The average values for radon concentration were found to vary from a minimum of 0.21 Bq/L to a maximum of 0.297 Bq/L. Heavy metals concentration were measured using an atomic absorption spectrometer. The mean concentrations of Pb, Cd, Co, Ni, Cu, Zn and Cr were 0.07, 0.009, 0.009, 0.043, 0.076, 0.079 mg/L and ND, respectively. Comparing the results with the literature, shows that the concentrations obtained were within the allowed limits of the agricultural and domestic use.